2020
DOI: 10.3390/ijms21051611
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Loaded Liposomes by Thin-Film Hydration and Microfluidic Procedures: Formulation Challenges

Abstract: Liposomes have been one of the most exploited drug delivery systems in recent decades. However, their large-scale production with low batch-to-batch differences is a challenge for industry, which ultimately delays the clinical translation of new products. We have investigated the effects of formulation parameters on the colloidal and biopharmaceutical properties of liposomes generated with a thin-film hydration approach and microfluidic procedure. Dexamethasone hemisuccinate was remotely loaded into liposomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Thus, formulation LP03 was selected as the final formulation, with lower levels of both surfactants (1.5% w / w of Tween 80 and 0.16% w / w of Span 60). The %LC of batch LP03 was calculated following Equation (2), which resulted in 30.22%, thus confirming the high loading capacity of this type of nanoencapsulation system [ 5 ] compared to other drug delivery systems like liposomes, in which Amin et al reached an LC of 12.6% [ 16 ].…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, formulation LP03 was selected as the final formulation, with lower levels of both surfactants (1.5% w / w of Tween 80 and 0.16% w / w of Span 60). The %LC of batch LP03 was calculated following Equation (2), which resulted in 30.22%, thus confirming the high loading capacity of this type of nanoencapsulation system [ 5 ] compared to other drug delivery systems like liposomes, in which Amin et al reached an LC of 12.6% [ 16 ].…”
Section: Resultsmentioning
confidence: 67%
“…Lipomers are a promising drug delivery system to improve the therapeutical balance of DEX in AA treatment, due to possible accumulation in the pilosebaceous unit, where the disease takes place, and under the hypothesis that the lipid nucleus increases the loading capacity. This fact leads to a higher drug concentration in the LPNCs, compared with similar particles without the lipidic core, for which the DEX loading capacity was about 1–2% [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, different approaches have been proposed to manufacture liposomes. 22 These include lipid film hydration, reverse phase evaporation, ethanol injection, ether injection, detergent removal, etc. Such methods are simple, rapid, and energy- and cost-efficient, ideal for laboratory-scale production and synthesis of smaller particle sizes with narrow particle size distribution.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Li et al reported that polymeric micelles with π–π conjugated moieties as lipophilic segments for delivering anticancer agents exhibited an LC value of 15% [ 23 ]. Al-Amin et al reported liposome particles with an LC value of 12% [ 44 ]. Therefore, PLHA-V x exhibited an excellent drug-loading capacity, with an LC value of 250%.…”
Section: Discussionmentioning
confidence: 99%